Učinek ortoze za gleženj in stopalo s sklepom z dvojno vzmetjo na vzorec in parametre hoje pri otroku s cerebralno paralizo - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2019)
Introduction: The article presents the case of a five-year-old child with cerebral palsy. Due to a walking pattern with toe walking and knee hyperextension (type 3 according to the Amsterdam classification) the child needed an ankle foot orthosis (AFO). We wanted to check how the pattern of walking with AFO with a dual pneumatic discs spring joint for dorsal and plantar flexion control (ddsAFO) differs from walking with the dynamic AFO (dAFO) with mobile elastomere joint in ankle and limited plantar flexion. Methods: We fitted the child with both AFO models and performed clinical gait evaluation, walking tests at 10 m and 6 minutes, and a computerised gait analysis using the same shoes. During the following six months the child used only the ddsAFO, then all tests and analyses were repeated with both models of AFO. We did not change any characteristics of AFO after the initial fitting. Results: The gait with ddsOGS was slightly faster and more fluid at the initial assessment. The computer analysis showed slightly better kinematic characteristics of the gait, although differences in walking distance and speed were small. After six months the gait pattern with ddsOGS was more symmetrical, with better alignment of the feet in the transverse and longitudinal plane, but with knee hyperextension still present. Conclusions: Clinical gait analysis showed that the use of ddsAFO is slightly more favourable compared to dAFO in terms of symmetry of gait pattern. For more reliable recommendations for ddsAFO use, a further study should be carried out on a larger sample of children with cerebral palsy, with more precise application and adjustment protocol, additional comparison to bare feet gait pattern and extended observation period for possible long-term effects.
Keywords: ankle foot orthosis; Cerebral Palsy; cerebralna paraliza; Child; dual pneumatic discs spring joint; gait; hoja; Orthotic Devices; ortoza za gleženj in stopalo; otrok; sklep z dvojno tlačno diskasto vzmetjo